EPISTEMOLOGI CORAK TAFSIR SUFISTIK - Lenni Lestari (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2014)
Many ideology interpretations of al-Qur’an have developed until today. One of them is mystical (sufistik) interpretation. This article will explore about epstemology aspects of mystical interpretation and a little bit of it history in grand mapping of al-Qur’an interpretation. In the last of this article will explain about how mysticism interpretation to be faced with verses (ayat) related to Fiqih, Science, Culture, and etc.